MAKNA BUDAYA OJIGI DALAM KEHIDUPAN ORANG JEPANG DEWASA INI (THE MEANING OF OJIGI CULTURE IN JAPANESE LIFE TODAY) - Elvie N. Piri (Kadera Bahasa, 2018)
Although Japan has progressed rapidly in the aspects of technology and science, yet its cultural values remain to be maintained. One of the cultural values that still exist until now is the expression of greeting gestured which is called ojigi.  Nevertheless it is questionable as the times to what extent the present generation signify the culture of ojigi in their daily lives. Do they still practice ojigi and understand the meaning? To answer this question, two methods used in collecting data were library research and questionnaire. It was conducted directly in Japan to high school students and other youth. Based on the results of data analysis it is found that (1) Since the beginning ojigi is a greeting culture that has a great significance and practiced faithfully in the Japanese life. It has changed in Japanese society however as the times. (2) based on a questionnaire survey of young Japanese, it has indeed changed to the culture of ojigi. Some people have replaced it by shaking hands which is a western culture. Some even do not practice ojigi anymore.